Early-onset Crohn's disease and autoimmunity associated with a variant in CTLA-4. Issue 12 (3rd November 2014) - Zeissig, Sebastian; Petersen, Britt-Sabina; Tomczak, Michal; Melum, Espen; Huc-Claustre, Emilie; Dougan, Stephanie K; Laerdahl, Jon K; Stade, Björn; Forster, Michael; Schreiber, Stefan; Weir, Dascha; Leichtner, Alan M; et al.
Abstract : Objective: IBD is a group of complex, systemic disorders associated with intestinal inflammation and extraintestinal manifestations. Recent studies revealed Mendelian forms of IBD, which contributed significantly to our understanding of disease pathogenesis and the heritability of IBD. Design: We performed exome sequencing in a family with Crohn's disease (CD) and severe autoimmunity, analysed immune cell phenotype and function in affected and non-affected individuals, and performed in silico and in vitro analyses of cytotoxic T lymphocyte-associated protein 4 (CTLA-4) structure and function. Results: A novel missense variant was identified in CTLA4 encoding CTLA-4, a coinhibitory protein expressed by T cells and required for regulation of T cell activation. The residue affected by the mutation, CTLA-4 Tyr60, is evolutionarily highly conserved, and the identified Y60C variant is predicted to affect protein folding and structural stability and demonstrated to cause impaired CTLA-4 dimerisation and CD80 binding. Intestinal inflammation and autoimmunity in carriers of CTLA-4 Y60C exhibit incomplete penetrance with a spectrum of clinical presentations ranging from asymptomatic carrier status to fatal autoimmunity and intestinal inflammation. In a clinically affected CTLA-4 Y60C carrier, T cell proliferation was increased in vitro and associated with an increased ratio of memory to naive T cells in vivo, consistent with impaired regulation of T cell activation. Conclusions: Our results support the concept that variants in CTLA4 provide the basis for a novel Mendelian form of early-onset CD associated with systemic autoimmunity. Incomplete penetrance of autoimmunity further indicates the presence of other genetic and/or environmental modifiers.